2005
DOI: 10.1016/j.drugalcdep.2004.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated everyday and prospective memory abilities of cigarette smokers and non-smokers: a web-based study

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 43 publications
(43 reference statements)
1
29
0
Order By: Relevance
“…A growing body of evidence suggests that chronic smoking, independent of substance abuse disorders, is associated with adverse effects on several domains of neurocognition, including executive skills, learning and memory, processing speed, and working memory (e.g., Ernst et al, 2001;Heffernan et al, 2005;Kalmijn et al, 2002;Paul et al, 2006;Razani et al, 2004;Richards et al, 2003). In a large cohort of community-recruited actively drinking and abstinent alcoholics, Glass et al (2006) found that both alcoholism and smoking severity were inversely related to neurocognitive function, and smoking severity (i.e., pack years) was a unique predictor of general intelligence and cognitive proficiency (i.e., an index of both speed and accuracy).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that chronic smoking, independent of substance abuse disorders, is associated with adverse effects on several domains of neurocognition, including executive skills, learning and memory, processing speed, and working memory (e.g., Ernst et al, 2001;Heffernan et al, 2005;Kalmijn et al, 2002;Paul et al, 2006;Razani et al, 2004;Richards et al, 2003). In a large cohort of community-recruited actively drinking and abstinent alcoholics, Glass et al (2006) found that both alcoholism and smoking severity were inversely related to neurocognitive function, and smoking severity (i.e., pack years) was a unique predictor of general intelligence and cognitive proficiency (i.e., an index of both speed and accuracy).…”
Section: Discussionmentioning
confidence: 99%
“…Meyer (Meyer et al, 1986) found that among multi-infarct dementia patients, improved cognitive function was related to cessation of smoking. Smokers also self-report more everyday and long-term prospective memory errors than non smokers (Heffernan et al, 2005). In sum, although there are beneficial acute effects of nicotine on cognitive performance, the long-term effects of smoking are clearly negative and seem most pronounced on measures of neurocognitive function that emphasize the ability to rapidly and flexibly process information.…”
Section: Introductionmentioning
confidence: 91%
“…This ability to remember to perform a delayed intention is critical to the efficiency of our everyday lives, has been shown to decline with advancing age (Maylor 1996) and is worse in smokers than non-smokers (Heffernan et al 2005;Heffernan et al 2010). PM, however, is not a unitary process; it involves encoding and maintaining an intention and retrieving and executing it at the appropriate moment in the future.…”
Section: Introductionmentioning
confidence: 99%